Effects of Touch Force Profiles and Waveforms of Electrostatic Tactile Feedback on Touchscreen Pan Operation. (8th November 2018) - Yan, Xuezhi; Li, Ruige; Sun, Xiaoying; Liu, Guohong
Abstract: Electrostatic tactile feedback has an important role in improving touchscreen operations and user experience. In this paper, panning performance under different forces and different waveforms were explored using subjective and objective experiments. The effects of electrostatic tactile feedback under one linear force and three non-linear force profiles with the fixed waveform were studied. The results indicated that panning accuracy, efficiency and user experience under exponential force was superior to those under linear, quadratic or logarithmic forces. Second, the effects of four different waveforms under exponential force were studied. Results indicated that panning performance was better with square wave, compared to those with sinusoidal, triangular or sawtooth waves. The relationship between panning time and index of panning difficulties was also explored and found to be in agreement with the Steering law and Meyer's law, with correlations of 0.9395 and 0.9397, respectively. The results suggest ways for designing touchscreens with tactile feedback that is useful in both research and end-user communities.